Capillary-Bridge Controlled Patterning of Stable Double-Perovskite Microwire Arrays for Non-toxic Photodetectors - Pi, Yueyang; Zhao, Jinjin; Zhao, Yingjie; Feng, Jiangang; Zhang, Chi; Gao, Hanfei; Wu, Yuchen; Jiang, Lei (Frontiers in Chemistry, 2020)
Single-crystalline lead halide perovskites with remarkable physical properties offer great potential in integrated optoelectronic applications, but are restricted by their instability and toxicity. To address these problems, various strategies including lead-free halide double perovskites with high stabilities of heat, light, and moisture have been developed. However, it still requires an efficient method to pattern single-crystalline double perovskite micro-/nanostructures with strict alignment and ordered orientation for the integration of optoelectronic devices. Here, our solution-processing approach employs capillary bridges to control the dewetting dynamics and confine the crystallization in the assembly of nontoxic Cs2AgBiBr6 microwire arrays. We demonstrate the strict alignment, high crystallinity, eliminated grain boundary, and ordered orientation of these as-prepared single-crystalline double perovskite microwire arrays. Based on these high-quality microwire arrays, we fabricate high-performance photodetectors with a responsivity of 1625 A W-1, on/off ratio of 104, and fast response speed of τdecay = 0.04 ms and τrise = 0.28 ms. The long-term crystallographic and spectroscopic stability of Cs2AgBiBr6 microwire arrays has also been demonstrated through the one-month exposure in air condition. Our strategy provides a new perception to fabricate stable perovskite microarrays for the integration of nontoxic optoelectronic devices.